Non-communicable diseases and maternal health: a scoping review - Tabassum Firoz; Beth Pineles; Nishika Navrange; Alyssa Grimshaw; Olufemi Oladapo; Doris Chou (BMC, 2022)
Abstract Background Non-communicable diseases [NCDs] are leading causes of ill health among women of reproductive age and an increasingly important cause of maternal morbidity and mortality worldwide. Reliable data on NCDs is necessary for accurate measurement and response. However, inconsistent definitions of NCDs make reliable data collection challenging. We aimed to map the current global literature to understand how NCDs are defined, operationalized and discussed during pregnancy, childbirth and the postnatal period.  Methods For this scoping review, we conducted a comprehensive global literature search for NCDs and maternal health covering the years 2000 to 2020 in eleven electronic databases, five regional WHO databases and an exhaustive grey literature search without language restrictions. We used a charting approach to synthesize and interpret the data.  Results Only seven of the 172 included sources defined NCDs. NCDs are often defined as chronic but with varying temporality. There is a broad spectrum of conditions that is included under NCDs including pregnancy-specific conditions and infectious diseases. The most commonly included conditions are hypertension, diabetes, epilepsy, asthma, mental health conditions and malignancy. Most publications are from academic institutions in high-income countries [HICs] and focus on the pre-conception period and pregnancy. Publications from HICs discuss NCDs in the context of pre-conception care, medications, contraception, health disparities and quality of care. In contrast, publications focused on low- and middle-income countries discuss NCDs in the context of NCD prevention. They take a life cycle approach and advocate for integration of NCD and maternal health services. Conclusion Standardising the definition and improving the articulation of care for NCDs in the maternal health setting would help to improve data collection and facilitate monitoring. It would inform the development of improved care for NCDs at the intersection with maternal health as well as through a woman's life course. Such an approach could lead to significant policy and programmatic changes with the potential corresponding impact on resource allocation.